Evaluation of MALDI-TOF MS in the microbiology laboratory - Anderson Fernandes Santos; Rodrigo Cayô; Lygia Schandert; Ana Cristina Gales (Sociedade Brasileira de Patologia Clínica, 2013)
Rapid identification of microorganisms by the clinical microbiology laboratory is of crucial importance for optimal patients' management and treatment. In general, bacterial identification by conventional methods requires 18-24 hours for colony isolation and at least 24 additional hours for species identification. New technologies in microbiology have focused on the rapid diagnosis of bloodstream infections, since they are associated with high morbidity and mortality rates.